2017
DOI: 10.1121/1.4985186
|View full text |Cite
|
Sign up to set email alerts
|

Masking release for hearing-impaired listeners: The effect of increased audibility through reduction of amplitude variability

Abstract: The masking release (i.e., better speech recognition in fluctuating compared to continuous noise backgrounds) observed for normal-hearing (NH) listeners is generally reduced or absent in hearing-impaired (HI) listeners. One explanation for this lies in the effects of reduced audibility: elevated thresholds may prevent HI listeners from taking advantage of signals available to NH listeners during the dips of temporally fluctuating noise where the interference is relatively weak. This hypothesis was addressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
2
18
0
2
Order By: Relevance
“…Moreover, Gatehouse, Naylor, and Elberling ( 2003 , 2006 ) suggested that if the noise is fluctuating with distinct temporal dips, fast-acting compression would provide differential amplification by applying more gain to the low-intensity glimpses of the speech than to the noise peaks, potentially leading to improved intelligibility. This prediction is consistent with recent results from Rhebergen, Maalderink, and Dreschler (2017) and Desloge, Reed, Braida, Perez, and D'Aquila (2017) , who established a link between increased speech audibility and improved speech intelligibility when applying fast-acting compression to speech in the presence of fluctuating background noise. On the contrary, compression can negatively affect the output SNR by reducing the speech level and overamplifying portions of the noise occurring in the speech gaps ( Alexander & Masterson, 2014 ; Hagerman & Olofsson, 2004 ; Naylor & Johannesson, 2009 ; Rhebergen et al., 2017 ; Souza et al., 2006 ).…”
Section: Introductionsupporting
confidence: 92%
“…Moreover, Gatehouse, Naylor, and Elberling ( 2003 , 2006 ) suggested that if the noise is fluctuating with distinct temporal dips, fast-acting compression would provide differential amplification by applying more gain to the low-intensity glimpses of the speech than to the noise peaks, potentially leading to improved intelligibility. This prediction is consistent with recent results from Rhebergen, Maalderink, and Dreschler (2017) and Desloge, Reed, Braida, Perez, and D'Aquila (2017) , who established a link between increased speech audibility and improved speech intelligibility when applying fast-acting compression to speech in the presence of fluctuating background noise. On the contrary, compression can negatively affect the output SNR by reducing the speech level and overamplifying portions of the noise occurring in the speech gaps ( Alexander & Masterson, 2014 ; Hagerman & Olofsson, 2004 ; Naylor & Johannesson, 2009 ; Rhebergen et al., 2017 ; Souza et al., 2006 ).…”
Section: Introductionsupporting
confidence: 92%
“…It is, however, unclear whether this would generalize to a broader range of interferers and speech stimuli. Recently, Desloge et al. (2017) proposed a system equalizing the short- and long-term energy of the signal, somewhat similar to instantaneous compression.…”
Section: Discussionmentioning
confidence: 99%
“…The noise was composed of five 100-ms bursts, separated by 100-ms silent gaps (corresponding to a 5-Hz repetition rate). Although rather artificial in nature, this noise envelope had the advantage that the sharp onsets and offsets and relatively long silent gaps emphasized the effects of compression time constants while ensuring that the consonant portion of speech would be affected by nonsimultaneous masking only ( Desloge et al., 2017 ; Wilson et al., 2010 ). White noise (bandlimited between 0 and 22050 Hz) was chosen as a carrier to maximize masking of high-frequency consonants and to reduce potential spectral splatter due to noise onsets and offsets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Audibility (in conditions with fluctuating maskers), frequency selectivity (in conditions with stationary noise), and temporal processing acuity (in conditions with speech interferers), have been identified as important factors affecting speech reception thresholds in noise (e.g. Desloge, Reed, Braida, Perez, & D’Aquila, 2017; Johannesen, Pérez-González, Kalluri, Blanco, & Lopez-Poveda, 2016; Oxenham & Simonson, 2009; Rhebergen, Versfeld, & Dreschler, 2006). Thus, a hearing evaluation that goes beyond pure-tone sensitivity and speech intelligibility in quiet would be expected to provide a more accurate characterization of a listener’s hearing deficits.…”
Section: Introductionmentioning
confidence: 99%